On the contrast between Germanic and Romance negated quantifiers - Robert Cirillo (Bucharest Working Papers in Linguistics, 2009)
Universal quantifiers can be stranded in the manner described by Sportiche (1988), Giusti (1990) and Shlonsky (1991) in both the Romance and Germanic languages, but a negated universal quantifier can only be stranded in the Germanic languages. The goal of this paper is to show that this contrast between the Romance and the Germanic languages can be explained if one adapts the theory of sentential negation in Zeijlstra (2004) to constituent (quantifier) negation. According to Zeijlstra’s theory, a negation marker in the Romance languages is the head of a NegP that dominates vP, whereas in the Germanic languages a negation marker is a maximal projection that occupies the specifier position of a verbal phrase. I will show that the non-occurrence of stranded negated quantifiers in the Romance languages follows from the fact that negation markers in the Romance languages are highly positioned syntactic heads.